Motivasi Kerja Memoderasi Pengetahuan Kerja dan Kompetisi Terhadap Kinerja - Irwani Nabhila; Tapi Rondang Ni Bulan; Teguh Setiawan (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aims to determine work knowledge and compensation for performance with work motivation as a moderation variable at PT Herfinta Farm And Plantation. In this study using a type of associative research witha quantitative approach. The population and sample in this study, namely employees of PT. Herfinta Farm andPlantation with a sample of 100 employees. The results in this study show that the variables of work knowledgeand compensation have a significant influence on performance. For work motivation variables that act asmoderation variables, in this study work motivation variables are able to moderate significantly between workknowledge variables but work motivation is not able to moderate compensation on performance.